Battleships: A Digital Game for the Development of Computational Thinking in Elementary School - Silva, Júlia Veiga da; Rosa, Yuri Silva; Foss, Luciana; Cavalheiro, Simone André da Costa (Anais do Workshop sobre Educação em Computação (WEI); 2023: Anais do XXXI Workshop sobre Educação em ComputaçãoDO - 10.5753/wei.2023.229541, 2023)
Computational Thinking is a method used to solve problems, based on the fundamentals and techniques of Computer Science, which is present in the norms on computing in Basic Education (complement to the BNCC). In a few years, schools should be implementing such norms. Thus, it is essential that didactic resources, tools, as well as adequate training be made available to the school network. Therefore, in order to contribute to this, this work proposes a digital game that deals with the organization and searches for information, in order to introduce some concepts and techniques of Computational Thinking; and it reports the results of training Basic Education teachers in the proposed activity.